Quantifying and analysing the non-collective bargaining benefits of NTUC - Neo, Aaron Chun Boon (2012)
The research is on one of the few; if not the only macro-focused labour union in the world on the non-collective bargaining benefits provided. National Trade Union Congress (NTUC) plays a vital role in maintaining Singapore’s comparative advantage with tripartism. If union benefits provided by NTUC, to its members (including the General Branch Members) are both timely and highly valued by them, it is similar to providing an additional wage differential to its members over non-members. This not only solves the free ridership problem of macro-focused unions, but it will also allow union members to receive a wage boost.